2017
DOI: 10.1038/s41598-017-03927-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Module-X2 and Carbohydrate Binding Module-3 on the catalytic activity of associated glycoside hydrolases towards plant biomass

Abstract: Cellulolytic enzymes capable of hydrolyzing plant biomass are secreted by microbial cells specifically in response to the carbon substrate present in the environment. These enzymes consist of a catalytic domain, generally appended to one or more non-catalytic Carbohydrate Binding Module (CBM), which enhances their activity towards recalcitrant biomass. In the present study, the genome of a cellulolytic microbe Paenibacillus polymyxa A18 was annotated for the presence of CBMs and analyzed their expression in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 80 publications
1
15
0
Order By: Relevance
“…Amongst the cellulose hydrolyzing enzymes, β-1,4-endoglucanases (EGs, EC 3.2.1.4) of GH5 family and β-glucosidases (BGLs, EC 3.2.1.21) of GH1 and GH3 family were represented in the genome. A xyloglucan-specific endoglucanase of GH74 family associated with CBM3 and X2 was also encoded in the genome, as was reported before 28 . Hemicellulose, being a complex polymer, requires the action of several enzymes for its degradation 29 .…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Amongst the cellulose hydrolyzing enzymes, β-1,4-endoglucanases (EGs, EC 3.2.1.4) of GH5 family and β-glucosidases (BGLs, EC 3.2.1.21) of GH1 and GH3 family were represented in the genome. A xyloglucan-specific endoglucanase of GH74 family associated with CBM3 and X2 was also encoded in the genome, as was reported before 28 . Hemicellulose, being a complex polymer, requires the action of several enzymes for its degradation 29 .…”
Section: Resultssupporting
confidence: 58%
“…A total of 45 carbohydrate binding modules (CBMs), which are generally associated with GHs for better substrate binding were also found in P. polymyxa A18. A detailed characterization of all CBMs of P. polymyxa A18, including their expression analysis and role in biomass hydrolysis, has been reported in our earlier study 28 . Categorization of CAZymes on the basis of functionality revealed that 76 CAZymes were predicted to be plant cell wall-degrading enzymes (CWDEs).…”
Section: Resultsmentioning
confidence: 86%
“…Based on the enzyme activity studies, endoglucanase with X2-CBM3 domains have a several fold increase in activity toward insoluble substrates. In substrate binding studies, the module X2 showed a higher affinity toward phosphoric acid swollen cellulose, whereas CBM3 showed a higher affinity toward crystalline cellulose (Avicel) (Pasari et al, 2017).…”
Section: Cellulases With Cbm In Aspergillus and Streptomycesmentioning
confidence: 99%
“…Although CBMs are most abundant among the soil isolates, majority of the proteins containing these modules do not have CAZYmes modules. CAZYmes without CBMs have been reported to show poor catalytic activities relative to their CBMs associated counterparts (Pasari et al, 2017). To enhance catalytic activity of certain CAZYmes lacking CBMs, the latter modules could be engineered in the enzymes.…”
Section: Carbohydrate-active Enzymes Enzyme (Cazyme) Repertoire and Smentioning
confidence: 99%